N,N′-Bis(4-bromophenyl)naphthalene-1,4-dicarboxamide N,N-dimethylacetamide disolvate - Jing, Lin-Hai (International Union of Crystallography, 2009)
The title compound, C(24)H(16)Br(2)N(2)O(2)·2C(4)H(9)NO, crystallizes in an anti C=O orientation. The two amide groups are twisted away from the naphthalene ring system by 62.67 (8) and 75.93 (7)°. The crystal packing is stabilized by N—H⋯O and C—H⋯O hydrogen bonds. Each of the dimethylacetamide solvent molecules is disordered over two positions, with occupancy ratios of 0.556 (7):0.444 (7) and 0.654 (7):0.346 (7).